2014
DOI: 10.1002/spe.2273
|View full text |Cite
|
Sign up to set email alerts
|

Netkit: network emulation for education

Abstract: Summary In the era of virtualization, virtual networking plays an important role. Besides production use, virtual networking can be effectively adopted in many other contexts where accurate emulation of functionalities is important, like testing before deployment, evaluation of what‐if scenarios, research, and, increasingly, didactics. In this paper, we describe our 10‐year experience in designing, implementing, using, and maintaining Netkit, an environment for simple, inexpensive, and lightweight network emul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 17 publications
0
4
0
2
Order By: Relevance
“…Software hosta, což často bývá celý operační systém, běží, jako by byl nainstalován na samostatné hardwarové platformě. Typicky je simulováno více takových virtuálních strojů na jednom fyzickém stroji (Pizzonia, Rimondini, 2016). Pro správnou funkci hosta je třeba, aby simulace byla dostatečně robustní, aby podporovala všechna vnější rozhraní hostovaného systému, což (vzhledem k druhu virtualizace) může zahrnovat i ovladače hardwaru .…”
Section: úVodunclassified
“…Software hosta, což často bývá celý operační systém, běží, jako by byl nainstalován na samostatné hardwarové platformě. Typicky je simulováno více takových virtuálních strojů na jednom fyzickém stroji (Pizzonia, Rimondini, 2016). Pro správnou funkci hosta je třeba, aby simulace byla dostatečně robustní, aby podporovala všechna vnější rozhraní hostovaného systému, což (vzhledem k druhu virtualizace) může zahrnovat i ovladače hardwaru .…”
Section: úVodunclassified
“…In Ref. , authors have analyzed implementation of virtualization and network emulation in educational institutions and have showed that this approach is well suited for teaching complex networking topics.…”
Section: Related Workmentioning
confidence: 99%
“…An example of CLI‐based emulator is Netkit . In Netkit, the user must obey Netkit's file directory structure and place the configuration files in the appropriate directories.…”
Section: Related Workmentioning
confidence: 99%
“…Network emulators provide a graphical user interface (GUI) or a command line interface (CLI) to allow users to specify their custom Internets. CLI‐based emulators include Netkit , Virtual Networks over LinuX, and Mininet . GUI‐based emulators include CORE , Cloonix , and GINI .…”
Section: Introductionmentioning
confidence: 99%